Receptor tyrosine kinase gene expression profiles of Ewing sarcomas reveal ROR1 as a potential therapeutic target in metastatic disease. Issue 5 (20th December 2015) - Potratz, Jenny; Tillmanns, Amelie; Berning, Philipp; Korsching, Eberhard; Schaefer, Christiane; Lechtape, Birgit; Schleithoff, Carolin; Unland, Rebekka; Schäfer, Karl-Ludwig; Müller-Tidow, Carsten; Jürgens, Heribert; Dirksen, Uta
Abstract : Receptor tyrosine kinases (RTKs) have provided molecular targets for the development of novel, prognosis‐improving agents in many cancers; however, resistances to these therapies occur. On the cellular level, one resistance mechanism is attributed to functional RTK redundancies and compensatory cross‐signaling, leading to perception of RTKs as signaling and target networks. To provide a basis for better exploitation of this network in Ewing sarcoma, we generated comprehensive qPCR gene expression profiles of RTKs in Ewing sarcoma cell lines and 21 untreated primary tumors. Key findings confirm broad‐spectrum RTK expressions with potential for signaling redundancy. Profile analyses with regard to patient risk‐group further revealed several individual RTKs of interest. Among them, VEGFR3 and TIE1 showed high‐level expressions and also were suggestive of poor prognosis in localized tumors; underscoring the relevance of angiogenic signaling pathways and tumor‐stroma interactions in Ewing sarcoma. Of note, compared to localized disease, tumors derived from metastatic disease were marked by global high‐level RTK expressions. Nine individual RTKs were significantly over‐expressed, suggesting contributions to molecular mechanisms of metastasis. Of these, ROR1 is being pursued as therapeutic target in leukemias and carcinomas, but un‐characterized in sarcomas. We demonstrate expression of ROR1 and its putative ligand Wnt5a in Ewing sarcomas, and of an active ROR1 protein variant in cell lines. ROR1 silencing impaired cell migration in vitro. Therefore, ROR1 calls for further evaluation as a therapeutic target in metastatic Ewing sarcoma; and described as a pseudo‐kinase with several isoforms, underlines these additional complexities arising in our understanding of RTK signaling networks. Highlights: Comprehensive gene expression profiles provide a baseline reference. Aspects of patient risk‐groups and metastasis are addressed. Individual receptor tyrosine kinases (RTKs) of therapeutic interest are revealed. ROR1 is identified as a potential therapeutic target in metastatic Ewing sarcoma. ROR1 underlines pseudo‐kinases and isoforms as additional complexities in RTK signaling networks.